Links between material and written sources in the study of the Early Middle Ages (Alpine Slavs) - Pleterski, Andrej (Arheološki vestnik, 1979)
Our knowledge of the Early Middle Ages (Alpine Slavs) leans almost exclusively on the basis of evidence supplied by written sources. For a good many years now the number of these sources has not changed and so knowledge of this period has stagnated. Luckily another source of knowledge of the past is growing every stronger, although a few decades ago it was insignificant, i. e. archaeological finds (material sources). However, material sources cannot tell us anything if we cannot set them in their historical framework. This can only be determined by linking up material and written sources. The need for closer co-operation between archaeologists and historians and for using the methods of working employed by both is becoming more and more obvious, as much outside Jugoslavia2 as within it.3 In Slovenia the number of early Slavic finds has already reached a level which would permit a first, though very modest, historical interpretation, linked with written sources. This also opens up the question of the methods to be used which might enable a close and fruitful link to be made. When two sides intend to pool their resources and work together, they usually first sort out their mutual relationship. Thus with archaeology and history. What kind of relationship exists between the two fields? Both archaeology and history have the same object and purpose of research:4 with the help of all known sources to reconstruct man’s past and its development and to determine the motive forces of this development and interpret it through them. Archaeology and history may study the same thing, but they differ from each other in the sources they draw from.5 Thus history developed through the study of written sources, archaeology through the study of material ones. Its own kind of techniques of investigation and its own interpretation of sources have enabled archaeology to stand as an independent subject6 which, because of the field of its interest, belongs within the framework of historical sciences.7 The ability to establish causality is that final condition necessary to turn some area of study into a real science. Historical materialism8 gave that ability to historical science.** Thus archaeology, as a component part of historical science, was given the possibility of historical reconstruction by the introduction of historical materialism into its working methods9 and this reconstruction is considered more and more by archaeologists to be the ultimate stage of archaeological research.10 A dialectic analysis of the past as a method of historical reconstruction relies on innumerable details which gain their full significance and sense only when brought together. Archaeology can therefore solve the causality of its subject only in combination with other historical sciences, especially with history itself. Thus the conviction that a historical problem can be solved only with the help of all the available sources (material, written and other) which touch on it is growing rapidly amongst archaeologists.11 Because of this those who try to fence archaeology12 away fromhistory are totally wrong (although this is understandable in a young field, which is still finding its feet and its sphere of activity) as they take13 from archaeology any ability to establish historical causes and laws, yet at the same time they involuntarily admit to doing this by their assertion that archaeology is not yet capable of determining the laws of the Qow of historical epochs.14 Only in combination with other fields (especially history) can archaeology possibly be a science. This is also a logical solution to the question of the relationship of archaeology to history, the question of subordination and superiority; “archaeology alongside history”, separate from it, is of necessity subordinate because of its limitations of perception; “archaeology wlth history”, linked with it, stands on a completely equal footing with history, as it is capable of a dialectic solution to the problems it faces. The possibility of collaboration between archaeology and history changes of course from historical period to historical period, depending on the amount of written and material sources available. The most fertile collaboration takes place in studying those periods where both kinds of sources are almost equally represented and so complement one another. This is especially true in Slovenia of the Classical period and the early Middle Ages. Although the general questions of uniting archaeological and historical evidence applies to both historical periods, a separate treatment for the latter period, from the appearance of the Slavs on the territory of the south-eastern Alps to the full development of feudalism, is both possible and necessary, as the significance of material sources for a historical reconstruction gradually decreases with time. This division is conditioned by features which previous ages did not have: a people settled here whose direct and immediate descendants are we Slovenes; this national continuity and continuity of habitation is accompanied by a continuity of culture, economics and social-political structure. Of course this continuity is not thought of as linear but as a curve which oscillates with the general course of historical development but which never breaks off. Besides this, one detail of methodology must not be forgotten: the position of history in later periods depends, if it is not interrupted, on earlier times and still retains elements of the latter to a greater or lesser degree.15 If a later period has left behind more varied sources of evidence than a preceding period which we wish to study, then we can use retrospective methods16 in our investigation. This kind of situation obtains in our examination of the early Middle Ages in Slovenia. This ability to study earlier periods by the use of later sources in used by archaeology as well as by history, but in a study of the early Middle Ages a retrospective use can be made only of written sources, as we only have extensive material sources up to the 11th century (archaeology of later periods is still in embryo form). On the other hand, the extent of written sources increases sharply with time and these are gradually able to fill the gap left by the lack of material finds and become capable of independently clarifying all aspects of man’s existence. Thus in a retrospective analysis written sources can additionally illuminate those problems whose solution was previously considerably or completely dependent on archaeological sources. This fact by itself demands a retrospective use of written sources for a complete interpretation of material sources so that the latter can be fully understood in their true context, as then we can trace the events they mark through the whole time of their duration (Table). A summary of the method of vertical (consecutive) links between archaeological (older) and written (later) sources is as follows: 1. The choice of a particular, limited area (for the archaeologist this is the area of the archaeological site he wishes to investigate). 2. To collect all archaeological data on the area and to gather together as many written sources as possible which refer to this area, from the first mention of it to the cadastral surwey of Francis I of Austria. 3. The entry of the results of the archaeological and historical topographical survey on the ordnance survey map of the area under study. 4. To find the village which proves a continuity of habitation from the early Middle Ages to today. If there is none, then present-day villages were founded only after the collapse of the early Slav villages. 5. The projection of older features of a later historical age back into the past. All this has looked at only one side of the union of archaeological and historical sources in the study of the early Middle Ages. The other side is represented by the linking up of material and written sources of the same period. This method is better known and has often been used to good effect. No special methodological approach is needed to use this. Of course it does demand a knowledge of the archaeological and written sources and the scientific methods used in working with them.19 By themselves material sources can immediately tell us a great deal about economics and everyday life, while they are less strong in the field of social questions (they can only reveal a greater or lesser degree of social differentiation, and they can usually tell us little the type and organisation of a society). They are useless for an examination of politi,. , questions.* In conjunction with written sources, however, they provide an indirect sou * of evidence, even extending into the sphere of social and political questions. The joining^ both kinds of sources can also aid us to gain a clearer picture of the religious and cultnr i side of the early Slav period.20 ral The possibility of a horizontal (contemporary) link between material and written sourc depends on their connections with historical events; written sources permit us to <jr.,eS conclusions about a historical event,21 while material sources are a physical reflection "p that event. Thus each complements and supplements the other. ot There now follow some practical examples of the successful combination of contempora™ material and written sources.22. 23. 24> 26 y At any event something more must be said on the attitude of archaeologists to the use of written sources. All our deductions about the combination of both kinds of sources proceed from the supposition that archaeologists use written sources in their work. In general it can be said that in principle they know the significance of supplementing and illuminating archaeological sources with written ones but in practice they use them very little and then all too often wrongly or to no purpose. A frequent mistake made by archaeologists is that they confuse historical literature with written sources, so that for them a historical interpretation, by a historian, is the same as the original written source itself.20 In this way written sources can “appear” which probably never existed.30. 32 Even when using original written sources one must be careful and exact, because every mistake made in the interpretation of a source multiplies when linked to material sources. The combination of both kinds of sources is wrong, although it appears to be logical and brilliant, but dangerous just because of this as it can become the starting point for further wrong interpretations.35 On the basis of the examples mentioned we can see that for a proper and successful combination of written and material sources the methods of working with both kinds of source must be mastered, as mistakes and failure arise if they are misunderstood. One must therefore be both archaeologist and historian. Finally let us once again summarise the methodological points for combining written and material sources in a study of the early Middle Ages (Alpine Slavs). 1. We can distinguish two groups of sources for a examination of the early Middle Ages, differing in time and content. The first group comprises contemporary, usually material and less often written sources up to a borderline between the 10th and 11th centuries; the second group is composed of older material and later written sources beginning at the end of the 10th and beginning of the 11th centuries (Table). 2. With reference to these two groups there are two possible, but different methods of combining material and written sources. The first group, the group of contemporary sources of both kinds, allows a horizontal (contemporary) combination, while the second group, of continuous, older material sources and later written ones, demands a vertical (consecutive) link between the two kinds of sources. 3. These two different ways of combining material and written sources also demand a different methodological approach. For a horizontal combination a knowledge of the methods of working with material and written sources is necessary; in a vertical combination, besides having a knowledge of the methods of working with both sources, it is necessary to master the method of retrospective analysis of written sources, as a special source with supplements the testimony of archaeological finds. 4. In examples where both horizontal and vertical combinations of material and written sources can be used in the resolution of a concrete problem, both methods of mutual complementation of the two sources must be used. The present methodological analysis aprings from the conviction that practical problems to which this combination method is applied can be solved systematically and therefore more easily, quickly and correctly only if one also has a suitable knowledge of theory and methodology. Without this point of departure one is dependent solely on intuitive links t,etween material and written sources. Established methodological starting points are undoubtedly still very rough and incomplete but they can spread and strengthen only through practical work — through the combination of material and written sources in the study of [he early Middle Ages. Likewise the method necessary for working with both sources cannot he learnt from books alone but from the work itself, as work is also study.